1994
DOI: 10.1021/om00024a024
|View full text |Cite
|
Sign up to set email alerts
|

Relative Binding Energies of Sterically Demanding Tertiary Phosphine Ligands to the Cp*RuCl (Cp* = .eta.5-C5Me5) Moiety. Thermochemical Investigation of Coordinatively Unsaturated Organoruthenium Complexes

Abstract: The enthalpies of reaction of (Cp*RuCl)4 (Cp* = i/5-C5Me5) with two sterically demanding monodentate tertiary phosphine ligands, leading to the formation of Cp*Ru(PR3)Cl (PR3 = P(CeHn)3 and ' 3) complexes, have been measured by anaerobic solution calorimetry in THE at 30 °C. The enthalpies of reaction associated with the rapid and quantitative reaction of the (Cp*RuCl)4 complex allow for a determination of relative ruthenium-phosphorus bond energy terms and, for the first time, enable a direct solution calorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 4 publications
4
24
0
2
Order By: Relevance
“…These reactions have been the subject of very detailed thermochemical investigations, which have shown that sterically demanding phosphane ligands exhibit the weakest RuϪPR 3 bonds. [31] There is an upper limit for the phosphane cone angle which allows the stabilization of [Cp*RuCl(PR 3 )] species. If the cone angle is too large this results in an inefficient RuϪPR 3 interaction.…”
mentioning
confidence: 99%
“…These reactions have been the subject of very detailed thermochemical investigations, which have shown that sterically demanding phosphane ligands exhibit the weakest RuϪPR 3 bonds. [31] There is an upper limit for the phosphane cone angle which allows the stabilization of [Cp*RuCl(PR 3 )] species. If the cone angle is too large this results in an inefficient RuϪPR 3 interaction.…”
mentioning
confidence: 99%
“…Cp*Ru(dmpm)Cl (where dmpm ¼ bis(dimethylphosphino) methane) is expected to have an electronic inuence at the metal center similar to P 2 N 2 ligands. Cp*Ru(dmpm)Cl was synthesized according to a published procedure, 75,76 and converted to Cp*Ru(dmpm)H by a reaction with excess NaBH 4 in ethanol.…”
Section: Comparative Studies Of Cp*ru(dmpm)hmentioning
confidence: 99%
“…Those quantitative studies involved collision-induced dissociation (CID) of mass-selected ions within the FTICR cell, and provided a lower limit for the Ru–PPh 2 H BDE of 16.6 kcal/mol. We noted the difficulty in comparing this absolute, gas phase value for an η 5 -indenyl system with BDE values for Ru–PR 3 available from solution calorimetry studies of tertiary phosphine substitutions at {Ru­(η 5 -Cp*)­Cl} 4 , given the dependence of the calorimetry-derived values on solvent and temperature, and the observed strong correlation of BDEs for the η 5 -Cp* system with steric, as opposed to electronic, properties of the tertiary phosphines studied . Ideally, a clearer picture of the relative binding energies of phosphines could be obtained by performing these painstaking CID studies on a broad range of analogous cationic complexes for a given half-sandwich system.…”
Section: Introductionmentioning
confidence: 99%